2021
DOI: 10.1177/2278533721989521
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors Affecting the Behavioral Intention of Visitors in Wine Festival: The Case of China Dalian International Wine and Dine Festival

Abstract: Wine-related festivals and events have emerged as a unique tourism product bringing not only economic value but also enhancing the brand image of a destination. China being the third largest wine-consuming country in the world has been organizing wine and food focused festivals which are participated by the residents as well as international visitors. Considering the size and scope of these events in China, this study explores the motivation behind participation in the wine festivals and investigates the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Likewise, Carvache-Franco et al [33] found that motivations for visiting the Red Crab festival in Ecuador included escape, socialization, art, food, local food, and knowledge. Similarly, Kabiraj et al [37] pointed out two motivations for attending the Dalian International Wine and Dining Festival. Those sets are Primary Motivations like tasting and buying wine and food, experiencing wine, learning food culture, and attending specific activities like wine and food tasting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Carvache-Franco et al [33] found that motivations for visiting the Red Crab festival in Ecuador included escape, socialization, art, food, local food, and knowledge. Similarly, Kabiraj et al [37] pointed out two motivations for attending the Dalian International Wine and Dining Festival. Those sets are Primary Motivations like tasting and buying wine and food, experiencing wine, learning food culture, and attending specific activities like wine and food tasting.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kabiraj et al [ 37 ] pointed out two motivations for attending the Dalian International Wine and Dining Festival. Those sets are Primary Motivations like tasting and buying wine and food, experiencing wine, learning food culture, and attending specific activities like wine and food tasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hong Kong Wine & Dine Festival founded in 2009 is a large-scale event that showcases a wide selection of wines, spirits, and gourmet food from around the world (Kabiraj, 2021). The main objective of the festival is to highlight Hong Kong's vibrant food and wine culture, offering a wide range of culinary experiences, wine tastings, and entertainment (King, 2022).…”
Section: Hong Kong Wine and Dine Festival -Hong Kongmentioning
confidence: 99%
“…Concurrently, the number of wine festivals in China has increased rapidly (Chinanews, 2019). Some researchers have examined the Chinese wine market (Camillo, 2012; Duan et al , 2018; Fountain et al , 2020; García-Cortijo et al , 2019; Li et al , 2011; Liu et al , 2014; Wang and Li, 2019; Zhang-Qiu et al , 2013) while several studies (Choe et al , 2018; Kabiraj et al , 2021; O’Regan et al , 2017, 2019) have focused specifically on Chinese wine festivals. Chinese wine festival attendees deserve more attention not only because China itself is a fast-growing consumer market for wine and wine festivals but also because it generates large tourist numbers for overseas wine tourism destinations (Gu and Huang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%